Evaluation of Structuring and Equalization Policy Implementation of Civil Servant Teachers Public Senior High Schools (SMA)andVocational Schools (SMK)) in Banda Aceh the Province of Aceh - *, Ismail; Akabar, Ma’ruf; Widodo, Suparno Eko (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study is to evaluate the implementation of the policy of structuring and equalization of civil servant teachers in public SMA and SMK in Banda Aceh City. This research uses Stake's Countenance evaluation model which consists of antecedent, transaction, and outcome. The results of this study indicate that the policy of structuring and equalization of teachers of public SMA and SMK in Banda Aceh has not been implemented in accordance with the expectations, which shows that there are advantages and disadvantages of teachers in almost every school on a particular subject, and these have impacts on the fulfillment of needs and the enhanchement of teachers’ competence.